WRECK THIS PICTURE BOOK - Smith, Keri (London : Puffin Books, 2020)
What if there were a book that changed every time you read it? Actually, every book does this. We are all part of the books we read, because our individual reactions, ideas, and emotions make the book whole, and these things are changing all the time. Keri Smith has helped millions of people free their creativity and find their own voice with her interactive books, and now she brings that sensibility to children and to the act of reading. This picture book is an invitation to honour your own vision and to welcome imperfection. Kids will discover that reading can engage all five senses, and that what they themselves bring to a book is an important contribution. (And of course they'll be invited to do a bit of harmless wrecking!)
4-7 years old.
Keywords: Creative thinking -- Juvenile literature; Picture books